2018
DOI: 10.1016/j.ibror.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of VGLUT1/2 in the inspiratory interneurons and GAD65/67 in the inspiratory Renshaw cells in the neonatal rat upper thoracic spinal cord

Abstract: HighlightsAbout half of the inspiratory interneurons in the ventromedial area of the third thoracic segment are glutamatergic.These glutamatergic interneurons may enhance the inspiratory intercostal motor activity.Inspiratory Renshaw cells exist in the ventromedial area of the third thoracic segments.Most of these Renshaw cells are GABAergic, and cause a single spike followed by ventral root stimulation at neonatal stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…VGlut1/2-expressing interneurons in Laminae III–V also control and modulate motor neurons. 61 As such, behavioural improvements after epoB treatment could be attributed to strengthening excitatory networks.…”
Section: Discussionmentioning
confidence: 99%
“…VGlut1/2-expressing interneurons in Laminae III–V also control and modulate motor neurons. 61 As such, behavioural improvements after epoB treatment could be attributed to strengthening excitatory networks.…”
Section: Discussionmentioning
confidence: 99%
“…Inspiratory and expiratory neurons are also found in the thoracic cord and it has been estimated that they outnumber bulbospinal respiratory neurons by 10 to 1 (Kirkwood et al, 1988). Both excitatory and inhibitory respiratory neurons have been described (Saywell et al, 2011;Iizuka et al, 2016Iizuka et al, , 2018. Propriospinal neurons that control limb movements, posture, or autonomic functions are also found in the cervical and thoracic cord.…”
Section: Propriospinal Neurons Shape the Pattern Of Respiratory Motormentioning
confidence: 99%
“…Studies of the rat phrenic nucleus have identified inspiratory, expiratory, and tonic firing inhibitory (GABAergic) interneurons (Marchenko et al, 2015;Ghali, 2018). The inspiratory inhibitory neurons include, but are probably not limited to, Renshaw cells that provide recurrent inhibition to phrenic and intercostal motor neurons (Kirkwood et al, 1981;Hilaire et al, 1983Hilaire et al, , 1986Lipski et al, 1985;Iizuka et al, 2018). Blocking GABAergic inhibition by spinal neurons alters the shape of the phrenic motor burst and increases activity during expiration (Marchenko et al, 2015).…”
Section: Propriospinal Neurons Shape the Pattern Of Respiratory Motormentioning
confidence: 99%
See 1 more Smart Citation
“…Using a voltage-sensitive dye, we further observed that this blockade of glycine and GABA A receptors increased inspiratory depolarizing signals in the interneuron area of the rostral thoracic spinal cord [ 2 ]. Using whole-cell patch clamp recording and the in situ hybridization method, we also showed that some inspiratory interneurons in the ventromedial portion of the rostral thoracic spinal cord are glutamatergic [ 3 ]. We have thus hypothesized that the enhancement of inspiratory motor activity comes from the enhancement of firing in these active inspiratory interneurons and/or the recruitment of inspiratory interneurons that give excitatory synaptic input to the motoneurons.…”
Section: Introductionmentioning
confidence: 99%